المواطنة وحق المشاركة في الحياة السياسية - بولقـــواس, إبتســـــام (revue mofakir; No 15 (2017): مجلـــة المفكــر, 2018)
إن المواطنة و باعتبارها رابطة سياسية و قانونية واجتماعية تربط الفرد بالدولة التي يقيم فيها وتمنحه جملة من الحقوق و التي من أهمها حق المشاركة في الحياة السياسية تطرح إشكالية رئيسية أساسية تتمثل في مدى حق كل من الأجنبي و مزدوج الجنسية في المشاركة في الحياة السياسية وذلك بالترشح لاكتساب العضوية في المجالس النيابية من عدمها . وتأتي دراستنا هاته من اجل بيان مفهوم المواطنة وتأثيرها على حق المشاركة في الحياة السياسية بالنسبة لكل من الأجنبي ومزدوج الجنسية .   Abstract: The citizenship as it is a political, legal and social link, it relates the individual with his state of residence and it gives him a number of rights, foremost of which is the right to participate in political life that poses a major problem in terms of the extent of both foreign and dual nationality persons’ right to participate in the political life by their candidature to, whether, gain the membership or not. Our study comes to illustrate the concept of the citizenship and its impact on the right of participation in political life for both foreign and dual nationality persons.